Konsep Garap Tari Duhnita Nari - Mutiara, Duwi (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This research was conducted focused on the concept of working on the duhnita nari dance using the traditional Malay dance foundation of West Pontianak, West Kalimantan. The method used in this research was descriptive qualitative with the aim of describing the framework containing the parts of forming a dance work. Dance works can be created through the process of searching for sources of ideas which can be obtained in many ways, for example looking for references from journals, reading or listening to folk tales or legends, reference books related to the theme of the dance that will be taken, raising issues that are problems for many people and other parts. From the kuntilanak character visualization journal based on an urban legend about the tragedy of a woman’s heartache which later became an inspiration for the dance artist to create a work.